2022
DOI: 10.54536/ajahs.v1i3.581
|View full text |Cite
|
Sign up to set email alerts
|

Close to School Supervision in Tanzania: Collective views on Teachers’ Job Performance

Abstract: This paper examined the effectiveness of close to school supervision in enhancing teachers’ job performance in Tanzanian public secondary schools. The study was guided by Path-Goal theory. This study adopted the qualitative approach using case study design and data were obtained from 32 informants. Semi-structured interviews and focus group discussion were the main data collection methods, and the data were thematically analysed. It was found that that the close to school education officers employed directive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Dokony, Signh and Arumugam (2020) in Chad found that supportive, achievement-oriented & participative leadership had a significant effect on employee satisfaction; directive Leadership behaviours did not show a significant impact on job satisfaction. Research conducted by Edgar, Mbwambo and Mngarah (2022) in Tanzania indicated that Ward Education Officer's use of directive supervision was effective to teacher's performance unlike supportive & participative supervision strategies. Rana, K'aol and Kirubi (2019) in Kenya concluded that supportive leadership style did not significantly influence employee performance while participative leadership had significant influence on employee performance.…”
Section: Introductionmentioning
confidence: 98%
“…Dokony, Signh and Arumugam (2020) in Chad found that supportive, achievement-oriented & participative leadership had a significant effect on employee satisfaction; directive Leadership behaviours did not show a significant impact on job satisfaction. Research conducted by Edgar, Mbwambo and Mngarah (2022) in Tanzania indicated that Ward Education Officer's use of directive supervision was effective to teacher's performance unlike supportive & participative supervision strategies. Rana, K'aol and Kirubi (2019) in Kenya concluded that supportive leadership style did not significantly influence employee performance while participative leadership had significant influence on employee performance.…”
Section: Introductionmentioning
confidence: 98%
“…Together, DHs and educators carry out the purpose of day-to-day teaching and learning activities (Chaula, 2023). According to Edgar et al (2022) educationalists today advocate for educators to receive support and guidance from their DHs to help them become the kind of educators they aspire to be. DHs are fully aware of their responsibilities in supporting TL through what is called clinical supervision where they receive training on how to provide support to their educators (Musundire & Dreyer, 2019).…”
Section: Meaning Of Supporting Teaching and Learningmentioning
confidence: 99%